Effectiveness of Peer-assisted learning in medical education: A meta-analysis study - Zhuoyang Li; Quan Wang; Junsong Wu (PLoS ONE, 2025)
The objective of this meta-analysis was to compare the effects of peer-assisted learning (PAL) and traditional teaching methods on the theoretical knowledge and practical skill education in clinical medicine by summarizing the relevant randomized controlled trial (RCT) studies reported to date. A comprehensive search was conducted across several medical literature databases, including PubMed, EMBASE, Springer, Ovid, Cochrane Library, China National Knowledge Infrastructure (CNKI), and China Biology Medicine Disc (CBMdisc). All pertinent articles, reviews, and references published from January 1970 to May 2023 were analyzed using Review Manager 5.4 software. A total of 81 RCTs were included in this analysis. The findings indicated that PAL surpassed traditional teaching methods in enhancing the transfer of theoretical knowledge and the acquisition of practical skills, especially in terms of student satisfaction and acceptance. It was also observed that, although PAL displayed advantages in certain areas, its effectiveness might not be substantial in fields demanding high levels of specialized knowledge. Furthermore, the reliability of the findings could be constrained by small sample sizes and inadequate implementation of blinding methods. Consequently, it is concluded that PAL is an effective and promising teaching method. Nonetheless, more rigorous research is required in the future to comprehensively explore the role of PAL in medical education.